Current extraction methods and potential use of essential oils for quality and safety assurance of foods - ALMEIDA-COUTO,JÉSSICA M.F. DE (2022)
Abstract Essential oils (EOs) or vegetable oils have become the focus of several studies because of their interesting bioactive properties. Their application has been successfully explored in active packaging, edible coatings, and as natural flavoring to extend the shelf life of various types of food products. In addition, alternative methods of extraction of EOs (ultrasound-assisted extraction, microwave-assisted extraction, pressurized liquid extraction and supercritical fluid extraction) have been shown to be more attractive than traditional methods since they present better efficiency, shorter extraction times and do not use toxic solvents. This review paper provides a concise and critical view of extraction methods of EOs and their application in food products. The researchers involved in the studies approached in this review were motivated mainly by concern about food quality. Here, we recognize and discuss the major advances and technologies recently used to enable shelf life extension of food products.